Assessment of Occupational Health and Safety Management System Implementation in General Hospital - Hastiti Lestari; Lutfi Nasrifah (Inovasi Analisis Data, 2024)
Objective: This study aims to assess the application of Occupational Health and Safety Management System (OHSMS) in Kertosono Regional General Hospital by identifying the obstacles and strategies that exist, as well as successful system implementation for health sector.Methods: This study utilized a mixed-methods design to assess OHSMS effectiveness and employee perceptions before and after implementation.Findings: Results show a statistically significant decrease in incidents at work after implementation of an OHSMS, which confirms that the global safety performance of this plant is affected by the OHSMS. By contrast, though inadequate instruction, lack of continuous leadership dedication and investment were some major obstacles to successful operation of OHSMS.Novelty: The findings from this study suggest the importance of structured safety management systems designed for public healthcare workers, and provide practical suggestions to bolster the effectiveness of OHSMS in Indonesia.Research Implications: The results also emphasize the importance of ongoing education and training, strong leadership support, as well as providing sufficient resources to promote a culture of safety in healthcare settings. Future research might instead seek upper bounds benefit of an OHSMS for safety or examine how technology can be integrated to provide monitoring, training function on a continuous basis.